Keterlibatan Santri dalam Persepsi Wacana Tiongkok - Dewi, Anitasa; Ansori, Feri; Hakam, Saiful (Masyarakat Indonesia, 2023)
Santris who have had the opportunity to go to China then face some contemplation, questions, and curiosity about what is really going on in the relationship between the two countries. Not all but some of them try to trace the substance and variations of Indonesians’ perceptions of China in the past. It’s like a philosophical romance where a child migrates to a foreign land but because of their migration, they become curious about their hometown. In scientific language, they try to slowly trace the existence of negative perceptions of China. They even unconsciously dismantle, although not frontally, the bad and negative image. Following Hong Liu’s (2015) opinion on the Chinese Metaphor, where China is used as a metaphor to express a sense of anxiety over domestic politics that is not going according to ideals, then, the santri are trying to dismantle the conflicting perceptions and narratives about China. For Indonesians, especially natives, Tiongkok as a nation-state is respected as a model country where leaders set an example so that the masses can work closely together. How the Chinese metaphor expresses the mood of the general public and anchors political and cultural thought in the early days of Indonesia as a country. Hong Liu even provides historical information that China for some Indonesian political elites was once used as an alternative form of modernity to the conception and practice of government politics that at that time still followed and emulated Western-derived systems and institutions. This study tries to apply a transnational approach to provide new insights into modern Asian History and regional transformation.